Conflicting Logics of Public Relations in the English NHS: A Qualitative Study of Communications and Engagement. (September 2019) - Carter, Pam; Dent, Mike; Martin, Graham
Since the formation of the National Health Service (NHS), all UK citizens have been entitled to access a universal health service, but radical changes to the NHS are now occurring. Although recent NHS policy claims that 'the NHS belongs to us all' and 'the NHS is a social movement', these collectivist rhetorical claims appear when such communitarian discourse is under threat, as NHS's Five Year Forward View tries to square the circle of efficiency, quality, and equity. Historically, patients and user-groups have formed support networks and social movements, and collectively campaigned for their voices to be heard by policymakers, clinicians, and managers. In contrast to the discourse of user movements, the field of marketing and public relations generally relies on the idea of the public as consumers rather than citizens. As complex governance arrangements blur the lines between public and private, concerns have been raised about how 'spin' associated with public relations might contravene accountability, communicative rationality, and deliberative or participatory democracy. Using qualitative methods, we conducted empirical research in two localities to explore the role of communications and engagement staff as they worked to 'transform' the NHS in line with the vision of the Five Year Forward View . We gathered documentary data and interview data from people whose roles required them to 'do engagement'. These staff came from a range of backgrounds, including professional marketing backgrounds, and many were unaware of emancipatory goals or user-led involvement and activism. Our analysis examines the competing logics of marketing and patient empowerment within a key stakeholder matrix document and that surfaced in participants' accounts of their engagement practices.